2022
DOI: 10.5194/mr-3-1-2022
|View full text |Cite
|
Sign up to set email alerts
|

Localising individual atoms of tryptophan side chains in the metallo-<i>β</i>-lactamase IMP-1 by pseudocontact shifts from paramagnetic lanthanoid tags at multiple sites

Abstract: Abstract. The metallo-β-lactamase IMP-1 features a flexible loop near the active site that assumes different conformations in single crystal structures, which may assist in substrate binding and enzymatic activity. To probe the position of this loop, we labelled the tryptophan residues of IMP-1 with 7-13C-indole and the protein with lanthanoid tags at three different sites. The magnetic susceptibility anisotropy (Δχ) tensors were determined by measuring pseudocontact shifts (PCSs) of backbone amide protons. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Shallow intersection angles are commonly observed when the same tag loaded with a different paramagnetic lanthanoid ion (such as Tb versus Tm ) is deployed at the same tagging site. Previous work, where we used the PCSs from three different tagging sites to determine the location of a solvent-exposed protein loop, showed that the localisation coordinates determined by PCSs were more accurate when all data encompassed PCSs measured with only a single paramagnetic metal ion . Therefore, we conducted the experiments with ubiquitin using Tm tags only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shallow intersection angles are commonly observed when the same tag loaded with a different paramagnetic lanthanoid ion (such as Tb versus Tm ) is deployed at the same tagging site. Previous work, where we used the PCSs from three different tagging sites to determine the location of a solvent-exposed protein loop, showed that the localisation coordinates determined by PCSs were more accurate when all data encompassed PCSs measured with only a single paramagnetic metal ion . Therefore, we conducted the experiments with ubiquitin using Tm tags only.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the ubiquitin data used in this work, the uncertainty of the PCS data associated with the amide protons of segments A–C was small (estimated to be less than 0.01 ppm). A straightforward approach that indirectly captures the effect of most of the sources of uncertainty on the localisation spaces relies on performing the tensor fits multiple times with random omission of a certain percentage of the PCSs .…”
Section: Discussionmentioning
confidence: 99%
“…This is largely due to the possibility to explicitly follow the dynamics of molecular systems with the full information about observables contained in the time series of positions and velocities within the framework of classical dynamics. The “translation” between the output from such a molecular dynamics (MD) simulation (positions and velocities as a function of time) is accomplished by virtue of statistical mechanics, in particular the correlation function formalism developed and introduced in the 1960s. …”
Section: Introductionmentioning
confidence: 99%
“…The orientation of an effective ∆χ tensor is predominantly governed by the steric and chemical environment of the tag and therefore difficult to predict. It has been observed many times, however, that different paramagnetic metal ions generally produce very similar ∆χ-tensor orientations, if the chemical structure of the tag and tagging site are the same (Su et al, 2008;Keizers et al, 2008;Man et al, 2010;Graham et al, 2011;Joss et al, 2018;Zimmermann et al, 2019;Orton et al, 2022). Similar ∆χ-tensor orientations lead to shallow intersection angles of the respective PCS isosurfaces.…”
mentioning
confidence: 99%
“…Shallow intersection angles are commonly observed when the same tag loaded with a different paramagnetic lanthanoid ion (such as Tb 3+ versus Tm 3+ ) is deployed at the same tagging site. Previous work, where we used the PCSs from three different tagging sites to determine the location of a solvent-exposed protein loop, showed that the localisation coordinates determined by PCSs were more accurate, when all data encompassed PCSs measured with only a single paramagnetic metal ion (Orton et al, 2022). Therefore, we conducted the experiments with ubiquitin using Tm 3+ tags only.…”
mentioning
confidence: 99%